Savitribai Phule: The First Woman Teacher In India - Mandal, Wg Cdr Ranjit Kumar (Journal of Advanced Research in English & Education; Vol 9 No 3 (2024): Journal of Advanced Research in English & Education, 2024)
Amma Savitribai Phule, was a social reformer who revolutionized women empowerment in India by educating women. She undertook an unprecedented as well as a bold initiative to make a beginning to educate the women of her time, especially the women of rural areas and belonging to marginalized communities. Till Savitribai initiated education of the women of India, not manyefforts were put in to include women in the formal education program, though the education of men started much earlier as a result of the British East India Company’s declaration, as the ruler of India then, through their Universal Education Policy, from the beginning of the Nineteenth Century. Born on January 3, 1831, in a well-to-do family of Shri Khandoji Patil in Naygaon village of Satara District of Maharashtra, Savitribai became the – “first woman teacher in India”. Savitribai was an inspirational poet and writer. She used her pen to inspire the women to empower themselves and break the shackles of slavery of the large number of the so-called untouchable people of the society.